PGR5/PGRL1 and NDH Mediate Far-Red Light-Induced Photoprotection in Response to Chilling Stress in Tomato - Wang, Feng; Yan, Jiarong; Ahammed, Golam Jalal; Wang, Xiujie; Bu, Xin; Xiang, Hengzuo; Li, Yanbing; Lu, Jiazhi; Liu, Yufeng; Qi, Hongyan; Qi, Mingfang; Li, Tianlai (Frontiers in Plant Science, 2020)
Plants experience low ambient temperatures and low red to far-red ratios (L-R/FR) of light due to vegetative shading and longer twilight durations in cool seasons. Low temperatures induce photoinhibition through inactivation of the photosynthetic apparatus, however, the role of light quality on photoprotection during cold stress remains poorly understood. Here, we report that L-R/FR significantly prevents the overreduction of the entire intersystem electron transfer chain and the limitation of photosystem I (PSI) acceptor side, eventually alleviates cold-induced photoinhibition. During cold stress, the increased FR activated photoprotection, including cyclic electron flow (CEF), protonation of PSII subunit S (PsbS) and de-epoxidation state of the xanthophyll cycle, energy-dependent quenching (qE) component of nonphotochemical quenching (NPQ), enzyme activity of Foyer-Halliwell-Asada cycle and D1 proteins accumulation. However, the L-R/FR –induced photoprotection was compromised in PROTON GRADIENT REGULATION5 (PGR5) and PGR5-LIKE PHOTOSYNTHETIC PHENOTYPE1A (PGRL1A) co-silenced plants and NADH DEHYDROGENASE-LIKE COMPLEX M (NdhM) -silenced plants in tomato during cold stress. Our results demonstrate PGR5/PGRL1- and NDH-dependent CEF mediate L-R/FR –induced cold tolerance by enhancing thermal dissipation and the repair of photodamaged PSII, mitigating overreduction of the electron carriers and ROS accumulation. It indicates that there is an anterograde link between photoreception and photoprotection in tomato plants during cold stress.